Basicities of primary arylamines and calculated amine nitrogen electronic charges - Leite, SRD (Editora Unesp, 1998)
Mulliken charges on nitrogen atoms were calculated for several arylamines, utilizing the AM1 Quantum Chemistry method, relating their values to experimental amine pKa Direct relation between pKa and nitrogen charges was found. The amines energies of protonation, calculated by the same method, also correlate directly with these charges.
Keywords: arylamines; basicity; N Mulliken charge; AM1